Stick or Dye: Evaluating a Solid Standard Calibration Approach for Point-Source Integrating Cavity Absorption Meters (PSICAM) - Wollschläger, Jochen; Röttgers, Rüdiger; Petersen, Wilhelm; Zielinski, Oliver (Frontiers in Marine Science, 2019)
Together with scattering, the process of absorption determines the propagation of light within the water column. It is influenced by the concentration and composition of optically active substances (phytoplankton, chromophoric-dissolved organic matter, and non-living particles). For this reason, the absorption coefficients of a water sample can provide corresponding information. However, the accurate determination of absorption coefficients in natural waters is often difficult due to the usually low concentration of absorbing material and the errors that scattering on particles introduce in the measurements. These problems can be overcome by instruments based on integrating cavities like the point-source integrating-cavity absorption meter (PSICAM). The accuracy of PSICAM measurements is to a large degree related to the accuracy of the measurement of the reflectivity inside its cavity, as this determines its mean optical path length. A reflectivity measurement (‘calibration’) is usually carried out by measuring a liquid dye (nigrosin) with known absorption coefficients, followed by bleaching and rinsing of the cavity. The procedure requires additional equipment like spectrophotometers and handling of a liquid standard. Therefore, it might be difficult or at least non-convenient under field conditions and is additionally a major obstacle for a potential automation of these systems. In the present study, an alternative calibration approach for a PSICAM is evaluated, taking advantage of a solid standard. The standard is characterized and its suitability for calibration is compared to that of a conventional, nigrosin-based reflectivity measurement. Furthermore, the application in an automated flow-through PSICAM system (HyAbS) used in the field is tested. The results show that the performance of the solid standard calibration is comparable to that of the nigrosine-based calibration. Furthermore, it improves the measurements of the automated system. Thus, due to its simplicity, the solid standard calibration might foster the use of PSICAM systems, which allow a more accurate determination of absorption coefficients in natural water samples compared to conventional spectrophotometric techniques. Furthermore, it will potentially facilitate further approaches to automate of these instruments.